Sagot :
Answer:
6. 7.2 sq m
7. 5.17
8. 11.2
9. 17.70
10. 14
Step-by-step explanation:
6. 43.2 ÷ 6 = 7.2 sq m
7. 15.51 ÷ 3 = 5.17
8. 78.4 ÷ 7 = 11.2
9. 63.5 ÷ 10 = 6.35
6.35 + 11.35 = 17.70
10. x = be the number
x = 5y + 4. - equation 1
x = 6y + 2. - equation 2
By elimination method, subtact 2 equations
[tex] \: \: \: \: x = 5y + 4 \\ - \: x = 6y + 2[/tex]
It will give us
0 = -y + 2
y = 2
Since y=2, substitute the value of y in either equation 1 or 2 it will give you the same number
So, I used equation 1
x = 5(2)+4
x= 10+4
x = 14